Gambaran Pengetahuan Siswa Madrasah Aliyah tentang Narkoba di Kepanjen Kabupaten Malang - Cesario Tesa Priantoro; Indung Susilo Sekti Kirono; Anastasia Stevie (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Drugs can lead to crimes such as theft, rape, and murder. The President of Indonesia has declare that Indonesia is in an emergency of drugs abuse. The largest drug users occurred in students with the highest increase at the senior high school level with a percentage of 63.34% or 24,326 students. Behavior of drug user is the result of all human experience and interaction with the environment manifested in the form of knowledge. This research was conducted to know the description of the students' knowledge about drugs in senior high school X Kepanjen district Malang Regency. This research is descriptive research with Cross sectional approach and the quantity of respondents was 54 respondents. Descriptive analysis results show that the majority of respondents have less knowledge with the number of 20 respondents (37%) because the environmental factors and less active role of Stakeholder, especially in the socialization of the knowledge about drugs. Conclusion of this research is the majority of respondents have less knowledge about drugs.